2016
DOI: 10.1016/j.celrep.2016.09.077
|View full text |Cite
|
Sign up to set email alerts
|

HSV1 MicroRNA Modulation of GPI Anchoring and Downstream Immune Evasion

Abstract: SummaryHerpes simplex virus 1 (HSV1) is a ubiquitous human pathogen that utilizes variable mechanisms to evade immune surveillance. The glycosylphosphatidylinositol (GPI) anchoring pathway is a multistep process in which a myriad of different proteins are covalently attached to a GPI moiety to be presented on the cell surface. Among the different GPI-anchored proteins there are many with immunological importance. We present evidence that the HSV1-encoded miR H8 directly targets PIGT, a member of the protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…Among these pathways, the GPI-anchor is considered to play an important role in the infection and pathogenesis of many viruses. For example, Enk et al found that the herpes simplex virus (HSV)-1-encoded miR H8 could target the GPI anchoring pathway, which further reduced the expression levels of several immune-modulating proteins and finally enhanced viral spread and enabled evasion of elimination by natural killer cells [6]. Amet et al demonstrated that a deficiency of GPI-anchor could inhibit the production of infectious HIV-1 and render virions sensitive to complement attack [1].…”
Section: Discussionmentioning
confidence: 99%
“…Among these pathways, the GPI-anchor is considered to play an important role in the infection and pathogenesis of many viruses. For example, Enk et al found that the herpes simplex virus (HSV)-1-encoded miR H8 could target the GPI anchoring pathway, which further reduced the expression levels of several immune-modulating proteins and finally enhanced viral spread and enabled evasion of elimination by natural killer cells [6]. Amet et al demonstrated that a deficiency of GPI-anchor could inhibit the production of infectious HIV-1 and render virions sensitive to complement attack [1].…”
Section: Discussionmentioning
confidence: 99%
“…HHV-1 encodes for miR-H8, which reduces the surface levels of ULBP2 and ULBP3. 98 The EBV-miR-BART2-5p directly targets MICB, 99 while EBV-miR-BART7 targets MICA. 100 MICB expression is also repressed by the CMV-miR-UL122 101 and by KSHV-miR-K12-7.…”
Section: Viral-encoded Mirs Enable Immune Evasion By Targeting Nkg2d-mentioning
confidence: 99%
“…Although most identified targets of the 27 mature HSV-1 miRNAs are viral transcripts, recent research has described roles for these viral miRNAs in targeting cellular transcripts to promote immune evasion, viral replication, cell proliferation, and pathogenesis [ 82 , 83 ]. One such example is the targeting of PIGT by miR-H8.…”
Section: Herpesvirusesmentioning
confidence: 99%
“…PIGT is an important component of the glycosylphosphatidylinositol anchoring pathway that allows proteins to be presented on the cell surface. MiR-H8 represses PIGT expression resulting in a reduction in presentation of many immune-related proteins, including NK-cell ligands and the viral restriction factor, tetherin [ 83 ]. Thus, by targeting PIGT, miR-H8 efficiently counteracts the host immune response at several key points.…”
Section: Herpesvirusesmentioning
confidence: 99%